Synthesis of the Algorithm of Adaptive Compensation of Nonlinear Distortions for Informational Systems - Shefer, Oleksandr; Shulha, Oleksandr; Ichanska, Nataliia; Kozelkova, Caterina (International Journal of Engineering and Technology, 2018)
An adaptive method of compensation of non-linear distortions was created in informational systems on the basis of usage the synthesized non-linear adaptive compensators for the expansion of a linear dynamic diapason of radio receiving devices that differs from the well-known ones, because it doesn’t lead to reduction of reliability of telecommunication systems both in apparatus and in functional meaning that allowed to increase the quality of their functioning. The usage of non-linear adaptive compensators allows getting the necessary meanings of parameters and the methods of connection of devices that are set to depress the non-linear distortions in those mentioned systems that will allow increasing the reliability of functioning of informational systems in 12% in general.